THE INFLUENCE OF CANDIDATE QUALITY AND CAMPAIGN ISSUES ON VOTING BEHAVIOR AT THE GOVERNOR ELECTION OF WEST SUMATRA INDONESIA - Adnan, M. Fachri (Fakultas Ilmu Sosial Universitas Negeri Padang, 2013)
The purpose of this research is to find out whether the candidate quality, campaign issues, respondent contact to the mass media, and regional bond are influence to voting behavior at the governor election of West Sumatra in 2005 in Padang City. Sample is determined by multistage random sampling. Data were collected by questionnaire and analyzed by multinomial logistic regression technique. The result of this research shows that the candidates quality and campaign issues is significantly influence to voting behavior at Governor of West Sumatra election 2005 in Padang. But the respondent contacts with mass media, and regional bond apparently did not affect on voting behavior at the election. It is imply that the candidate quality and the campaign issues is important to understand voting behavior at the West Sumatera GovernorÂ election. Keywords : voting behavior, candidate quality, campaign issues, regional bond